Reliability based design optimization of coupled acoustic-structure system using generalized polynomial chaos. (December 2017) - Dammak, K.; El Hami, A.; Koubaa, S.; Walha, L.; Haddar, M.
Highlights: An analytical formulation and numerical implementation of the response of coupled structure-acoustic system were performed. A probabilistic analysis is addressed to account for variability of different parameters. A reliability based design optimization (RBDO) using the generalized polynomial chaos (gPC) is proposed. The optimum safety factor (OSF) method combined with the gPC procedure is applied to the coupled acoustic-structure system in order to reduce the computational cost of the classical approach of RBDO. Graphical abstract: Abstract: In this work, an analytical formulation and numerical implementation of the response of the coupled structure-acoustic system were performed. The acoustic pressure inside the cavity as well as the plate displacement are analyzed. This study is combined with a probabilistic analysis to account for variability of different parameters, considered as random variables, which are material properties. A reliability based design optimization (RBDO) using the generalized polynomial chaos (gPC) is addressed. In order to reduce the computational cost of the classical approach of RBDO problem, the optimum safety factor (OSF) method coupled with the gPC procedure is applied to the coupled acoustic-structure systems. Numerical examples showed the effectiveness and efficiency of the OSF based on gPC for the reliability optimization of the structural-acoustic system with probabilistic random variables.